La Expresión Oral - Jesús Ramírez Martínez (Universidad de La Rioja, 2013)
An approach to the oral expression as a communicative skill is proposed, which needs to be developed from pragmatic and teaching perspectives. The colloquial aspect of the oral expression is the reason nhy it has been considered an ordinary skill in everyday life, and for this reason it has not been paid enough pedagogic attention. Therefore, a pedagogic approach is considered absolutely necessary. It comes from an inductive concept which, through certain real and shared experiences lived by the author, can allow us to understand and test teaching activity models. As a result can begin to construct our own theory about this communicative and scientific approach concerning this universal oral expression.